Expanding the capabilities of people with disabilities in disaster risk reduction. (March 2019) - Ton, Khanh That; Gaillard, J.C.; Adamson, Carole Elizabeth; Akgungor, Caglar; Ho, Ha Thanh
Abstract: The vulnerability paradigm widely adopts a resource-based approach for examining disaster risk. From this perspective, the vulnerability of people in disasters arises from a lack of resources. It can be argued that frameworks under this approach focus mainly on the means (i.e. resources) but overlook the ends (i.e. what people are capable of doing or being to cope with disasters). Furthermore, the resource-based approach neglects the processes or factors that are involved in converting resources to meaningful activities and states. Therefore, to bridge these gaps, this paper suggests a human capability-centred framework as an alternative approach to better understand disaster risk facing people. Examples of people with disabilities, who are among the groups most at risk in the face of disasters, will be used to scrutinise the framework. Accordingly, disaster risk facing people with disabilities is viewed as a consequence of the deprivation or lack of capabilities to cope with disasters and this deprivation results from a shortage not only of resources, but of enabling conversion factors. Thus, to reduce disaster risk for them, it is critical to expand their capabilities to cope with disasters. This can be achieved by fostering meaningful participation of people with disabilities in decision-making processes impacting on their well-being, not only in times of disasters, but also in everyday life. Examining the disaster risk facing people with disabilities, through the lens of the capability approach, has also raised possibilities of applying this approach for understanding disaster risk facing other groups of people in society.